Cholestatic Liver Injury After Biliary Reconstruction Impairs Transplanted Islet Viability and Function. Issue 8 (23rd April 2015) - Hata, T.; Sakata, N.; Yoshimatsu, G.; Tsuchiya, H.; Fukase, M.; Ishida, M.; Aoki, T.; Katayose, Y.; Egawa, S.; Unno, M.
<x xml:space="preserve">Abstract</x> Islet autotransplantation following total pancreatectomy differs from allograft transplantation with respect to the requirement of biliary reconstruction. Although it is known that careful consideration should be given to postoperative cholestatic liver injury after biliary reconstruction, its direct effects on transplanted islets have not been completely elucidated. In this study, we developed a murine model of postoperative cholestatic liver injury after biliary reconstruction with islet autotransplantation that involved syngeneic intraportal islet transplantation into chemically induced diabetic mice and common bile duct ligation. We assessed the viability and function of the transplanted islets. The impaired viability of transplanted islets and increased blood glucose levels indicated restoration of the diabetic state after common bile duct ligation in this murine model. Furthermore, impaired islet viability and function occurred earlier in the transplanted islets than in the surrounding liver tissues, which was consistent with the faster and higher expression of oxidative stress markers in the transplanted islets. Transplanted islets may be more vulnerable to oxidative stress caused by cholestatic liver injury than the surrounding liver tissue. Therefore, patients should be intensively managed after total pancreatectomy with islet autotransplantation to preserve viability and function of the transplanted islets.